Train to Somewhere - Bunting, Eve, 1928-2023; Himler, Ronald (New York : Clarion Books, 1996)
In the late 1800s, Marianne travels westward on the Orphan Train in hopes of being placed with a caring family.
Keywords: Orphans -- Fiction; Orphan trains -- Fiction